Effect of feed restriction on performance, stress and clinical welfare indicators of ross 308 broiler chickens - Maake, Mmatlou Christinah (My University, 2024)
This study investigates the effect of feed restriction on the growth performance, stress, and welfare indicators of Ross 308 broiler chickens aged 1 to 35 days. The experiment aimed to determine the impact of feed restriction on (1) growth performance, (2) welfare clinical indicators, and (3) gut morphometrics, carcass characteristics, meat quality, and sensory evaluation. A total of 270-day-old Ross 308 broiler chicks were randomly assigned to three treatment groups, with two replications per group. Each treatment group consisted of two separate sets of chicks ,which were independently managed and subjected to the same experimental conditions. The data were analyzed using the General Linear Model (GLM) procedure and Analysis of Variance (ANOVA), with significance considered at the 5% level. The results showed that feed restriction improved daily feed intake, body weight gain, and feed conversion ratio (P<0.05) in comparison to ad libitum feeding. Welfare indicators, including pecking behaviour, body condition, and feather condition, were significantly affected by feed restriction (P<0.05), while gait score, footpad, and skin condition were unaffected (P>0.05). Feed restriction also influenced (P<0.05) gut organ weight and length, as well as carcass weight and chicken pieces, but had no effect on pluck weight or dressing percentage. Meat quality analysis revealed no significant changes in color or pH, while tenderness and juiciness were positively influenced (P<0.05), with no impact on flavor or shear force. In conclusion, feed restriction in Ross 308 broiler chickens improved growth performance, affected specific welfare indicators, and influenced certain carcass and meat quality traits. The results suggest that feed restriction can be used to optimize growth and meat quality while maintaining reasonable welfare standards, although it has mixed effects on certain welfare indicators.
Thesis (M. Agricultural Management (Animal Production)) -- University of Limpopo, 2024
Keywords: Feed restriction; Ross 308 broiler chickens; Growth performance; Welfare indicators; Carcass characteristic; Sensory evaluation; Broilers (Chickens); Feeds -- Research; Sensory evaluation; Feed utilization efficiency; Poultry -- Feed utilization efficiency